1) x^4 - 6x^2 + 8 = 0
x^4 - 6x^2 = - 8
x^2(x^2 - 6) = - 8
x^2 = - 8 или x^2 - 6 = -8
x^2 = - 8 x^2= - 8 + 6
x^2 = - 2
2) (2x - 1)^2 - (2x - 1) - 12 = 0
(2x - 1)^2 - (2x - 1 ) = 12
4x^2 - 4x + 2 - 2x + 1 = 12
4x^2 - 6x = 12 -1 -2
4x^2 - 6x = 9
2x ( 2x - 3) = 9
2x = 9 или 2x - 3 = 9
x = 9/2 2x= 9+3
x = 4,5 2x = 12
x = 6
Объяснение:
1) x^4 - 6x^2 + 8 = 0
x^4 - 6x^2 = - 8
x^2(x^2 - 6) = - 8
x^2 = - 8 или x^2 - 6 = -8
x^2 = - 8 x^2= - 8 + 6
x^2 = - 2
2) (2x - 1)^2 - (2x - 1) - 12 = 0
(2x - 1)^2 - (2x - 1 ) = 12
4x^2 - 4x + 2 - 2x + 1 = 12
4x^2 - 6x = 12 -1 -2
4x^2 - 6x = 9
2x ( 2x - 3) = 9
2x = 9 или 2x - 3 = 9
x = 9/2 2x= 9+3
x = 4,5 2x = 12
x = 6
Объяснение: